2011
DOI: 10.1063/1.3643435
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics according to the channel length and magnetic fields of cylindrical Hall thrusters

Abstract: Performance characteristics of low power cylindrical Hall thrusters are investigated in terms of the length of the discharge channel. Thrust, efficiency, discharge current, and propellant utilization are evaluated for different channel lengths of 19, 22, and 25 mm. It is found that the propellant utilization and ion energy distribution function are strongly associated with the channel length. Increase of thrust and efficiency are also found with increasing channel lengths. These characteristics of the thruster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
(10 reference statements)
1
20
0
Order By: Relevance
“…The average / can be higher than if is produced in such a way that /2 / /2 , or 2 / / . it is noteworthy that the existence of ions with energy higher than the anode voltage was experimentally observed in previous works [8,[16][17][18][19][20].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The average / can be higher than if is produced in such a way that /2 / /2 , or 2 / / . it is noteworthy that the existence of ions with energy higher than the anode voltage was experimentally observed in previous works [8,[16][17][18][19][20].…”
mentioning
confidence: 88%
“…The detailed description of the experimental set-up is found in Refs. [14][15][16][17][18]. Throughout the experiment, an electric potential of 300 V was applied to the anode and the mass flow rate of Xe gas supplied through the anode was either 4.0 or 10.0 sccm.…”
mentioning
confidence: 99%
“…On the other hand, a large multiply charged Xe ion fraction 9,14 has been clearly confirmed in cylindrical-type Hall thrusters (CHTs) for low-power applications. [15][16][17][18][19] As will be discussed below, we report on the significant influence of the different magnetic field geometries, which are obtained through a simple modification of the coil polarity, on the thruster performance and beam characteristics. These characteristics include the angular distribution of the ion beam, the ion current, the electron current, and the fraction of multiply charged ions.…”
Section: Effect Of Magnetic Field Configuration On the Multiply Chargmentioning
confidence: 99%
“…1,6,7 It was experimentally found that a longer cylindrical region improves thrust and efficiency, ion energy, and in particular propellant utilization. 5 Compared with a full cylindrical Hall thruster where the anode surface is leveled with the inner magnetic core surface, it is expected that a small localized region just in front of the anode (i.e., the annular region, as mentioned above) may provide enhanced ionization and propellant utilization. This is due to high local neutral density from the propellant gas supplied through the anode near which magnetic field lines converge to yield electron trapping.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10] Previous works reported that the structural feature of CHTs reduces the interaction between the plasma and the dielectric channel wall such as electron transport, heating, and wall erosion, which is effective especially as the Hall thruster scales down to a few hundred watts level. 4 The operational principle of the CHT is based on the closed E Â B electron drift and acceleration of non-magnetized ions by electrostatic potential, similarly to the conventional annular type Hall thruster.…”
Section: Introductionmentioning
confidence: 99%